Adversarial legalism the American way of law - Kagan, Robert A. (Harvard University Press, 2019)
American dispute resolution is more adversarial, compared with systems of other economically advanced countries. Americans more often rely on legal threats and lawsuits. American laws are generally more complicated and prescriptive, adjudication more costly, penalties more severe. Here, Kagan examines the origins and consequences of this system